2021
DOI: 10.1177/01640275211017268
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Race in Relations of Social Support to Hippocampal Volumes Among Older Adults

Abstract: Evidence suggests social support may buffer brain pathology. However, neither its association with hippocampal volume, a marker of Alzheimer’s disease risk, nor the role of race in this association has been fully investigated. Multiple regression analyses examined relations of total social support to magnetic resonance imaging-assessed gray matter (GM) hippocampal volumes in the total sample ( n = 165; mean age = 68.48 year), and in race-stratified models of African American and White older adults, adjusting f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 61 publications
(76 reference statements)
0
2
0
Order By: Relevance
“…Of interest, recent research has suggested that social support may serve as a buffer against volume loss and cognitive decline in minoritized groups. 48,49 Certainly, future research in larger, more diverse samples will be needed to disentangle the complex relationships between race/ethnicity, neighborhood disadvantage, other contextual factors and contributors to cognitive function, and neuropsychological functioning.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of interest, recent research has suggested that social support may serve as a buffer against volume loss and cognitive decline in minoritized groups. 48,49 Certainly, future research in larger, more diverse samples will be needed to disentangle the complex relationships between race/ethnicity, neighborhood disadvantage, other contextual factors and contributors to cognitive function, and neuropsychological functioning.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies in recent years have identified divergent cognitive and behavioral phenotypes among patients with seemingly homogenous epilepsy syndromes that relate to sociodemographic, clinical, and network characteristics. [31][32][33][34] In 2020, a task force was assembled by the International League Against Epilepsy and the International Neuropsychological Society to develop a consensus-based empirically driven No MTS (62) 88 ( 49) 84 ( 41) 79 ( 46) 56 (48) Abbreviations: ADI = Area Deprivation Index; ASMs = antiseizure medications; MTS = mesial temporal sclerosis. a Values are reported as median (interquartile range) or n (%); quintile 1 = least disadvantaged, quintile 5 = most disadvantaged.…”
Section: Neuropsychological Outcomesmentioning
confidence: 99%